Solid and compact biomaterial, method for production thereof, and kit for filling bone cavity

By developing a composite biomaterial composed of PMMA and β-TCP, the shortcomings of existing bone substitutes in integration with bone tissue are solved, and good integration of biomaterials and bone regeneration are achieved, with improved mechanical and capillary performance.

CN119677549APending Publication Date: 2025-03-21TECRES SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380059171.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-23
Filing Date
2023-09-06
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing bone substitutes have shortcomings in integration with bone tissue, resulting in problems of implant relaxation and mechanical failure.

Method used

A solid and compact biomaterial was developed, using a composite material of a first structural component composed of PMMA and β-TCP and a soluble second ceramic component to improve the biocompatibility, mechanical properties and capillary properties of the biomaterial through its porous structure and specific component ratios.

Benefits of technology

The biomaterial is able to effectively integrate with bone tissue, improve bone regeneration capabilities, has improved mechanical properties and capillary properties, is suitable for filling large bone gaps and reduces the risk of relaxation of the implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677549A_ABST
    Figure CN119677549A_ABST
Patent Text Reader

Abstract

A composite biocompatible osteoinductive and / or osteoconductive biological material, the biological material comprising a first structural component and a second ceramic component wherein the biological material is present in solid form and is compact; a method, system for obtaining said biological material, said system comprising said biological material in solid form and a similar material in liquid form for filling a bone gap or cavity, and a bone substitute comprising at least one variant of a biological material according to the present application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid and compact biomaterial that can be used to fill bone gaps, even large bone gaps.

[0002] The invention also relates to a method for producing the biomaterial, as well as a system or a kit made of the biomaterial in solid form and in fluid form for filling bone gaps.

[0003] The present invention also relates to a bone substitute comprising the biomaterial according to the present invention.

[0004] The biomaterial is able to optimally integrate with the biological system it interfaces with, thereby exhibiting improved properties in terms of bioinductivity, bioconductivity, and mechanical properties. Background Art

[0005] In the field of biomaterials, especially biomaterials that can be used in orthopedic and surgical fields to fill cavities or gaps of various sources and types, most of the biomaterials currently used are ceramic and / or polymer biomaterials, which are basically used to fix prostheses or serve as bone substitutes.

[0006] Among these polymeric biomaterials are, for example, acrylic bone cements, which may consist of polymethyl methacrylate (PMMA) and / or methyl methacrylate (MMA), and reabsorbable cements, which are used when the supporting function they must fulfil is of limited duration.

[0007] PMMA is a plastic resin present in acrylic bone cement, which is a two-component medical product consisting of a powder and a liquid that are kept separate until used by a doctor. The powder is made of approximately 85% PMMA polymer (methyl methacrylate polymer) and the liquid is made of 98% MMA (methyl methacrylate monomer). Other components, such as radiopacifying agents, catalysts and antibiotics may be present in small amounts. Once mixed together, PMMA powder and MMA liquid form a ductile and injectable fluid substance that acquires and increases viscosity over time and solidifies in about 10 minutes by heating to about 70-80°C. The reaction that occurs is a polymerization reaction of MMA monomers, which in turn become polymers or PMMA. The solid obtained is actually PMMA containing the reagents originally present, as well as a portion (about 5-10%) of unreacted MMA. Bone cements formed in this way are generally used to support metal joint prostheses, such as in the patient's leg, for many years (even more than 20 years if necessary). Subsequently, the more mechanically robust the bone cement is, the longer it will hold up over time, with the unfortunate possibility of structural failure being rare. In this regard, there are standards specific to PMMA, such as ISO 5833 and ASTM F 451-21, which define the minimum mechanical compressive resistance that the product must possess.

[0008] However, an important disadvantage of acrylic bone cement is that it does not integrate with the bone tissue surrounding the implantation site, but rather results in the formation of a fibrous sheath or mantle at the interface between the biomaterial itself and the bone tissue, leading to the risk of implant laxity.

[0009] However, in the case of resorbable cements, they are more biocompatible than acrylic cements but have poorer mechanical tolerance.

[0010] There are also biomaterials that have microcavities and macrocavities of a certain size in order to promote bone regeneration therein. However, the mechanical properties of these materials are effective for certain applications but not for others. In addition, once polymerized, they may exhibit internal inhomogeneities, which affects their capillary capacity.

[0011] Known bone substitutes may also comprise appropriately deantigenated human bone tissue or ceramic materials.

[0012] However, the former may resorb early or fail mechanically, leaving dangerous empty spaces at the site of previous implantation, while the latter cannot guarantee adequate structural support in most cases but are dissoluble in the human body. In addition, they can be infected, are very expensive and difficult to produce, and may cause immune rejection.

[0013] Known ceramic materials are mainly composed of mono-ceramic materials (such as hydroxyapatite) or bi-ceramic materials (such as hydroxyapatite + tricalcium phosphate) or poly-ceramic materials (such as a mixture of different ceramics or different calcium salts, hydroxyapatite + tricalcium phosphate + calcium sulfate type).

[0014] The use of one or another ceramic material depends on the dissolution rate of the material itself after implantation in the human body: if a very slow or almost zero resorption is desired, hydroxyapatite will be used, while calcium sulfate, on the contrary, ensures a very fast resorption. Ceramic mixtures with different solubilities will exploit this aspect depending on the therapeutic needs.

[0015] However, ceramic materials are very fragile and can break easily, releasing dangerous fragments. Therefore, similar to human bone products, they must always be used in conjunction with a metal support (e.g., plates, fixators, etc.). Even during dissolution, they produce fragments that can migrate and cause severe inflammatory reactions.

[0016] Hybrid materials for human implantation are also known comprising water-soluble plastic polymers, for example formed from polylactic acid and polyglycolic acid, either alone or in mixtures of the same or in racemic form, and TCP and HA. However, such materials, once implanted, are doomed to disappear completely over time, since all of their constituent parts are completely soluble.

[0017] Such materials have not produced very positive results and are primarily used to create resorbable screws rather than bone substitutes.

[0018] Therefore, there is a need for biomaterials that can be used as bone substitutes, fully able to integrate with the bone tissue surrounding the implantation site, in such a way as to allow the reestablishment of blood circulation within it, while having improved mechanical properties, even in the case of large lesions or bone gaps. Summary of the invention

[0019] Therefore, the technical task of the present invention is to improve the prior art.

[0020] Within the scope of this technical task, one object of the invention is to develop solid and compact biomaterials which have improved mechanical properties.

[0021] Another object of the present invention is to develop biomaterials with improved capillary properties.

[0022] According to one aspect of the present invention, a biomaterial according to claim 1 is provided.

[0023] A further object of the present invention is to develop a simple and practical method for producing solid and compact biomaterials.

[0024] According to one aspect of the present invention, a method according to claim 10 is provided.

[0025] A further object of the present invention is to develop a system or kit comprising a solid and compacted biomaterial, and a fluid biomaterial for filling bone gaps.

[0026] According to one aspect of the present invention, a system or a kit according to claim 15 is provided.

[0027] According to one aspect of the present invention, a bone substitute according to claim 18 is provided.

[0028] The dependent claims refer to preferred and advantageous forms of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Any person skilled in the art will better understand these and further advantages from the following description and the accompanying drawings, given as non-limiting examples, in which:

[0030] Figure 1 Some examples of biomaterial constructions according to the present invention are shown;

[0031] Figure 2 Some further examples of biomaterial constructions according to the invention are shown;

[0032] Figure 3 An example of implanting the biomaterial according to the present invention (comprising acrylic resin and / or PMMA, and TCP) into an animal is shown;

[0033] Figure 4 Four samples (n°ln°4) are shown tested for performance analysis in terms of mechanical properties;

[0034] Figure 5 Shows Figure 4 Details of sample No. 3;

[0035] Figure 6 Shows the Figure 4 Mechanical properties of sample 1 (left) compared with sample 3 (right);

[0036] Figure 7The following diagram is shown, where for Figure 4 Four samples n°ln°4, the test time (in seconds) is shown on the abscissa and the load (in Newton) is shown on the ordinate.

[0037] Fig. 8A and 8B shows an enlarged detail of an embodiment of a biomaterial according to the invention, the biomaterial being formed of PMMA and β-TCP, and of PMMA alone, the β-TCP having been dissolved and / or resorbed,

[0038] Fig. 9 A graph is shown relating to an example of a distribution of selected particles having a nominal particle size of 200-500 microns, with the size in microns on the abscissa and the number in percentage on the ordinate,

[0039] Fig. 10A and 10B shows an embodiment of a biomaterial according to the invention formed of pre-implantation PMMA and β-TCP, respectively, and an embodiment of a biomaterial according to the invention formed of PMMA alone, wherein the β-TCP has been dissolved and / or resorbed,

[0040] Fig.11 An example of a cranial prosthesis that can be manufactured using a biomaterial according to an embodiment of the present invention, such as a customized cranial prosthesis, is shown.

[0041] Fig.12 shows an example of a spacer device, such as a shoulder device, which can be made of a biomaterial according to an embodiment of the present invention,

[0042] Fig.13 Three samples prepared with the same resin (first component, e.g. PMMA) are shown, which were polymerized using the following conditions: (A) under vacuum, e.g. at a pressure of -0.8 bar, (B) at an ambient pressure of 1 bar, and (C) at a pressure of 10 bar, e.g. in an autoclave.

[0043] Fig.14 Shows Fig.13 A cross-sectional view of a sample of which the portion is coated with petroleum jelly such as Stringy ( Fig.14 of the top row) and carbon black ( Fig.14 ). DETAILED DESCRIPTION

[0044] In this specification, biomaterial refers to the following materials: the material can interface with the biological system to increase, treat or replace any tissue, organ or function of the body; bioinductivity refers to the ability of the biomaterial to induce neoformation of the tissue interfaced with the biomaterial; bioconductivity refers to the ability of the biomaterial to produce an appropriate support that allows the colonization of tissue progenitor cells interfaced with the material and can ensure their survival and proliferation.

[0045] The biomaterial according to the present invention has biocompatible properties and is bioinductive and bioconductive.

[0046] The biomaterial according to the invention is suitable for filling gaps or bone cavities, for example gaps or bone cavities of large size, such as large lesions caused by combat injuries, large tumors, large traumas (eg caused by motor vehicles, etc.).

[0047] It is to be understood, however, that the characteristics of the present biomaterial make it generally useful for filling bone lesions or gaps, for example, areas of the body that are subject to high or greater loads than other areas.

[0048] Therefore, the biomaterial according to the invention is suitable for use as a bone substitute, for use in bone gaps or cavities, or even for functional restoration of (tissue) where it is necessary to insert, replace or repair bone tissue.

[0049] The biomaterial according to the present invention is in the form of a preformed solid having a three-dimensional spherical, hemispherical, discoid or discoidal, polyhedron, parallelepiped, hexahedron, truncated cone or truncated pyramid, cone or pyramid, parallelepiped, rod or plate (splint), wedge-shaped, wedge-shaped or irregular three-dimensional shape. The shape and / or configuration is the shape and / or configuration it presents when it is ready for use (e.g., when implanted in the human body).

[0050] Therefore, the biomaterial according to the invention is solid and preformed and is provided to the surgeon in this state for his use. In fact, it is a product prepared in a factory rather than by a doctor.

[0051] Therefore, in fact, it is a product that can be provided to the surgeon as is, and / or can be inserted into the corresponding bone cavity as is or after grinding (to better adapt to a specific shape and / or size) in order to compensate for bone loss, and / or inserted into a specific implantation position.

[0052] As a solid and preformed material, the biomaterial according to the invention also constitutes a bone substitute - in at least one embodiment. Therefore, unless otherwise specifically stated, the properties described for the biomaterial are also to be understood as belonging to the bone substitute itself.

[0053] Bone substitute refers to a preformed solid that can be used to fill lesions, gaps or bone cavities, or to repair bone tissue function where it is necessary to replace or repair bone tissue, such as large gaps or bone cavities, large lesions caused by combat injuries, large tumors, large trauma (e.g., caused by car accidents, etc.).

[0054] Bone substitute also refers to a prosthetic or spacer device 100 to be permanently or temporarily implanted in a bone seat or space in the human body to replace bone tissue or joints that have been damaged and / or compromised due to pathology or infection.

[0055] Thus, the biomaterial according to the present invention can constitute a cranial prosthesis 100 for reconstructing cranial injuries, or even a preformed spacer device 100 for removing infected prostheses and subsequently treating infections present in the bone cavity, thanks to the structure and porosity of the biomaterial, which allows medical substances (such as specific antibiotics) to be absorbed and subsequently released in the body.

[0056] With the biomaterial of the present invention, which is solid and preformed, small devices of a few grams up to 100 grams or more, if necessary, can be produced.

[0057] As better defined below, when referring to a bone substitute in this specification, it is meant to be made of the following first structural component: the first structural component is permanent when used and cannot be resorbed in the human body, wherein the first structural component comprises an organic, plastic, and / or polymer material and comprises interconnected pores, wherein the interconnected pores comprise pores and / or tubules having a diameter of less than 100 microns, microcavities having a size of less than 100 microns, and macrocavities having a size between 100 and 500 microns, or between 200 and 500 microns, or between 300 and 500 microns, or between 100 and 2000 microns, or between 200 and 2000 microns, or between 300 and 2000 microns, or greater than 250 microns and up to 2000 microns, or greater than 250 microns and up to 500 microns, or between 500 and 2000 microns, or greater than 500 microns and up to 2000 microns. In the bone substitute according to the present invention, these microcavities and macrocavities can be formed during the polymerization and / or solidification step of the first structural component and become hollow after the second ceramic component (encapsulated in at least some of the first structural component) dissolves and / or solubilizes. Alternatively, these microcavities and macrocavities can be prepared in different ways, depending on the requirements.

[0058] Furthermore, the second component can only be partially housed in the microcavities and macrocavities. This means that, in particular, the macrocavities are at least only partially occupied by the second component.

[0059] Therefore, before the second component is dissolved, the biomaterial according to the present invention presents such microcavities and macrocavities, but they are not hollow (or not completely hollow) because the second component is at least enclosed in some microcavities and macrocavities, preferably in all microcavities and macrocavities. Therefore, at this stage, the cavity acts as a housing seat for the second component.

[0060] Dissolution of the second component can occur before or after implantation, depending on the specific needs.

[0061] pass Figure 1 and Figure 2 Examples of possible configurations of biomaterials according to the invention are illustrated.

[0062] The biological material thus forms a solid artefact. An artefact is a product resulting from manual or mechanical manufacture.

[0063] This biomaterial is therefore in solid form and is compact, as better explained below.

[0064] It will be appreciated from this disclosure that the biomaterial according to the present invention, before implantation and at least for a period of time after implantation, is a composite and / or mixed biomaterial in terms of the materials constituting the biomaterial.

[0065] The biomaterial according to the present invention actually comprises a first structural component and a second ceramic component.

[0066] The second ceramic component is soluble, for example soluble when in contact with a fluid (eg a biological fluid) during use.

[0067] The first structural component is permanent and forms a structural matrix, which is a characteristic of the biomaterial according to the present invention. This means that once implanted in the human body, the first structural component cannot be reabsorbed, nor can it be dissolved or corroded by the influence of fluids (such as biological fluids or other fluids). Therefore, the first structural component is insoluble and maintains its original shape unchanged.

[0068] The first structural component and / or structural matrix is ​​shaped like a "sponge".

[0069] In fact, the first structural component is porous. In particular, the biomaterial comprises "open" pores, meaning that they allow liquids to pass through by capillary action. This, together with the other properties highlighted below, allows the preservation of the biological activity of the surrounding tissue and promotes the regeneration of bone tissue within it.

[0070] The pores are interconnected and arranged in a random but uniform manner throughout the volume occupied by the first structural component.

[0071] The porosity may include a plurality of "canaliculi", eg, tubules less than 100 microns in diameter, which are formed during the manufacturing steps of the biomaterial itself.

[0072] The tubules are also in communication and interconnection with each other and with the remaining pores of the biomaterial according to the present invention.

[0073] Thus, the first structural component is both compact and porous.

[0074] The first structural component comprises at least one plastic and / or polymeric component, or is made of at least one plastic and / or polymeric component. The material is natural biocompatible. In one embodiment of the invention, the first structural component comprises a plastic material, such as a plastic or acrylic or methacrylic resin, or a plastic or acrylic polymer, or a bone cement made of polymethyl methacrylate (PMMA) and / or a copolymer based on methyl methacrylate, or a thermoplastic polymer, polyethylene, polypropylene, polyester, a thermoformable polymer, or other similar materials.

[0075] The presence of the above-mentioned "tubules" is an indispensable requirement so that the various materials constituting the first structural component can promote bone regeneration inside it. In fact, as described, the material of the first structural component has a structure and / or material state corresponding to a "sponge", i.e., for example, completely similar to spongy bone tissue. The spongy feature is precisely due to the presence of pores and / or tubules inside the first structural component.

[0076] In fact, if the first structural component is not porous and / or tubules are not present, the second ceramic component - at least the second ceramic component present deep within the first structural component - is completely inaccessible to fluids (such as water or biological fluids) for dissolution.

[0077] After this, the second ceramic component dissolves, with the concomitant formation of empty spaces within the first structural component, making it possible to trigger a positive biological response, which ensures bone regeneration within the biomaterial.

[0078] In one embodiment of the invention, the first structural component consists (only) of at least one of the above-mentioned materials.

[0079] The first structural component is made of an organic material.

[0080] In at least one embodiment of the present invention, the first structural component is not a polysaccharide and / or the biomaterial according to the present invention does not comprise a polysaccharide.

[0081] The first structural component includes a microcavity and a macrocavity.

[0082] These micro- and macro-cavities are hollow during use, at least for a period of time after implantation.

[0083] Therefore, these micro- and macrocavities may also be part of the pores of the biomaterial.

[0084] In at least one embodiment of the present invention, such microcavities and macrocavities may be made hollow by dissolving the second ceramic component in the first structural component to leave empty spaces.

[0085] The size of the microcavity is less than 100 microns.

[0086] Preferably, the macrocavity size or diameter is between 200 microns and 500 microns, or 300 microns and 500 microns and (in decreasing amounts or percentages, even larger diameters, up to) 2000 microns, or between 100 and 500 microns, or between 100 and 2000 microns, or between 200 microns and 2000 microns, or 300 microns and 2000 microns, or greater than 250 microns up to 2000 microns, or greater than 500 microns up to 2000 microns. The macrocavity presents a substantially spheroidal configuration. The macrocavity is the result of the presence of the second component (e.g., particles of the second component), which is incorporated into the structural component, which dissolves and hollows out the microcavity.

[0087] The microcavities and macrocavities are uniformly distributed throughout the volume constituted by the biomaterial and / or the first structural component of the biomaterial according to the present invention.

[0088] The tubules are also uniformly distributed throughout the volume formed by the biomaterial and / or the first structural component and are uniformly distributed relative to the positions of the microcavities and macrocavities.

[0089] The second ceramic component is made of an inorganic material.

[0090] It is therefore understandable why the biomaterial according to the invention is composite: it is a "hybrid" material made of a plastic and / or polymeric material and a ceramic material.

[0091] The second ceramic component is in the form of a powder having a size less than 100 microns, and a granular material having a size between 100 microns and 500 microns, or between 100 microns and 2000 microns, or between 200 microns and 500 microns, or between 300 microns and 500 microns, or between 200 microns and 2000 microns, or between 300 microns and 2000 microns, or greater than 250 microns up to 2000 microns, or greater than 500 microns up to 2000 microns.

[0092] According to at least one embodiment of the invention, the granular material has a particle size between 100 and 2000 microns and is a statistical mixture of particles with different particle sizes.

[0093] For example, a typical distribution for a granular material with a nominal particle size of 200-500 microns is as follows:

[0094] Table 1a: Particle size distribution

[0095]

[0096]

[0097] For example, a typical distribution for particulate matter with a nominal particle size of 300-500 microns is reported below:

[0098] Table 1b: Particle size distribution

[0099]

[0100] The second ceramic component includes at least one calcium salt.

[0101] The calcium salt may include compounds based on calcium phosphate (CP), calcium sulfate (CS), calcium carbonate (CC), and the like.

[0102] In the calcium phosphate-based compound, at least one or more of the following compounds may be present: monocalcium phosphate monohydrate (MCPM), monocalcium phosphate anhydrous (MCPA), monocalcium phosphate dihydrate (DCPD), monocalcium phosphate anhydrous (DCP), octacalcium phosphate (OCP), α-tricalcium phosphate (α-TCP), β-tricalcium phosphate (β-TCP), hydroxyapatite (HA), tetracalcium phosphate (TTCP).

[0103] In at least one embodiment of the present invention, the second ceramic component comprises at least two or more calcium salts.

[0104] According to one embodiment of the present invention, the second ceramic component comprises only calcium phosphate or a mixture of calcium phosphate and calcium sulfate and / or calcium carbonate and / or hydroxyapatite.

[0105] For example, according to one embodiment of the present invention, the second ceramic component comprises calcium sulfate and / or calcium carbonate and / or hydroxyapatite and / or tricalcium phosphate.

[0106] According to an example of the present invention, the second ceramic component may be composed of a mixture of hydroxyapatite and calcium carbonate, for example, according to a ratio of HA:CC=30%:70%.

[0107] The presence of (at least) one calcium salt is very important since it enhances the bio-tolerance of the biomaterial when in use and its integration into the surrounding tissue in which it is used.

[0108] For example, if the biomaterial is used to be partially inserted into bone tissue and partially into medullary fat tissue, the biomaterial itself integrates with them at the interface of these (different) tissues by incorporating their progenitor cells (such as osteoblasts), without the fibrotic encapsulation of the typical hostile rejection reaction. Subsequently, these neo-tissue cells develop into mature lamellar tissue, expanding into the empty space left by the dissolution of the second ceramic component, promoting true osteointegration.

[0109] The choice of different calcium salts is also related to differences in their dissolution / dissolution times. The different solubilization times of the calcium salts allow the physician to adapt the biomaterial to the biological recovery time of the bone impacted by the implant, which is different for all types of bones and also depends on the mechanical loads acting on the implant site.

[0110] For example, the regeneration of the skull, which is virtually unloaded, proceeds at a different rate than the regeneration of the femur or tibia, which in contrast are subject to interaction forces of many kilograms.

[0111] consider Fig. 8A and 8B , respectively, illustrate the initial conditions of solid biomaterials ( Fig. 8A ), wherein TCP particles of a second ceramic component are embedded in the tubules and / or generally in the pores of the first structural component, in this case PMMA. Note the "sponge-like" nature of PMMA.

[0112] However, Figure 8BThe final state of the biomaterial is shown, i.e., after the TCP granules are dissolved by a fluid (e.g., water, liquid or biological fluid), which reaches the granules through a network of tubules and dissolves them. In the cavities (which are vacant due to the dissolution of the second ceramic component), bone tissue settles, since these cavities (called macrocavities) have a size that allows the formation of mature lamellar bone.

[0113] Based on their dissolution rates, we report a list of calcium phosphate based compounds in Table 2. The dissolution rate at the tip of the arrow is lower, while the dissolution rate at the origin of the arrow is higher.

[0114] Table 2:

[0115]

[0116] In Table 3 below, we report some solubility values ​​in water.

[0117] Table 3:

[0118] Calcium salt Solubility in water <![CDATA[Calcium sulfate (CaSO4)]]> 2g / l <![CDATA[Calcium carbonate (CaCO3)]]> 0.014g / l <![CDATA[Tricalcium phosphate (Ca3(PO4)2 TCP)]]> 0.002g / l <![CDATA[Hydroxyapatite Ca 10 (PO4)6(OH)2 HA]]> Virtually insoluble

[0119] The second ceramic component occupies the space inside the microcavities and macrocavities of the first structural component.

[0120] In particular, the granules of the second ceramic component occupy the macrocavities, whereas the powder occupies the microcavities (and possibly the small tubes) due to its size.

[0121] Naturally, this is an approximate position, since in fact it is the presence of the second component during the polymerization and / or solidification phase of the first component that determines the position (ie at least part of the pores, and / or micro- and macro-cavities) in which the second component encloses itself.

[0122] Subsequently, powder dissolution leads to microcavity patency, whereas (subsequent) dissolution of the particles determines macrocavity patency.

[0123] The tubules are formed independently of (and in advance of) the patency of the micro- and macro-lumens and hence independently of the formation of complete pores in the biomaterial of the invention, since they are formed during the polymerization step of the first component, when dissolution of the second component has not substantially occurred.

[0124] The first structural component constituting the biomaterial according to the present invention plays a structural function and has certain mechanical properties that are far superior to those of known materials.

[0125] Moreover, being insoluble, it is permanently present in the implant (only the second ceramic component will be solubilized and / or resorbed, in any case it will be at least partially eliminated from the biomaterial and / or replaced after implantation). According to the invention, this condition provides the biomaterial according to the invention with mechanical properties that remain virtually unchanged over time, since they depend (at least in most cases and / or when the second ceramic component is completely dissolved) on the amount and / or type of insoluble plastic material present. Therefore, the need for additional mechanical supports (plates, external fixators, etc.) is less pressing or even useless.

[0126] Furthermore, the biomaterial is not brittle, and no fragments are generated during the solubilization of the second ceramic component. In fact, the biomaterial of interest has a higher elasticity than bone or even prior art materials: its elastic modulus is in fact 0.8-3.0 GPa, depending on the percentage and / or type of the second ceramic component. In contrast, current materials of ceramic nature have significantly greater rigidity and are more brittle. For example, the elastic modulus of hydroxyapatite is between 40 and 117 GPa, making it much harder than bone tissue, which has a modulus of about 18 GPa.

[0127] As mentioned above, the second ceramic component is soluble and therefore has the ability to dissolve and / or gradually dissolve after contact with water and / or various liquids and / or biological fluids, for example once the biomaterial is implanted in the human body in use.

[0128] Thus, during use, a first time period can be distinguished, during which the biomaterial is implanted in the human body, the biomaterial being made of the first structural component and the second ceramic component (the latter being at a percentage of 100%, i.e. not yet dissolved, solubilized and / or resorbed). This is followed by a second time period, which follows the first time period, during which the second ceramic component begins to dissolve and / or solubilize upon contact with water or a liquid, such as a biological liquid, and a third time period (also the final time period), in which the biomaterial according to the invention consists only of the first structural component, since the second ceramic component has completely dissolved.

[0129] The bone substitute of the invention, at least in one embodiment, corresponds to the biomaterial in its third stage (final stage), or in its full bioinductive and bioconductive potential.

[0130] During the second time period, the second ceramic component is present in a smaller and smaller percentage as it dissolves and thereby separates from the first structural group and elutes with the fluid (eg, biological fluid).

[0131] Furthermore, during the second and third time periods, bone regeneration of bone tissue around the implant begins inside the first structural component as the second ceramic component dissolves and / or solubilizes, leaving empty spaces corresponding to the microcavities and macrocavities housing the second ceramic component. Furthermore, due to the specific structure of the biomaterial according to the present invention, it has been seen that blood circulation is also reestablished within the first structural component, ensuring perfect adhesion of the regenerated bone tissue to the material constituting the first structural component. In fact, during the third time period, it is almost no longer possible to distinguish the material of the first structural component from the newly formed bone tissue. Ultimately, once the calcium salt is completely lost, the biomaterial is chemically identical to the first component (e.g., bone cement). However, from histological observations, it can be seen that the biomaterial according to the present invention maintains a much better compactness with bone tissue than conventional bone cements. This is because it is a completely "functioning" tissue, because, as previously described, it is perfused with fluids, blood, and substances useful for its development and growth. Therefore, the second and third time periods occur in the human body after implantation, and in its initial configuration, it is found as defined by the first time period, i.e., consisting of the first structural component and the entire second ceramic component.

[0132] As mentioned above, the second ceramic component is resorbable. In fact, once the second ceramic component dissolves and / or solubilizes, it is resorbed by the body. However, even if completely dissolved, it leaves clear traces of its past presence. These traces may be present at the surface and in the depth of the structural component, in the form of fine roughness covering small tubes, microcavities and macrocavities. This surface modification acts as a real "texture", greatly increasing the affinity between biological tissue and synthetic tissue (just the structural component).

[0133] In fact, the biomaterial and / or bone substitute according to the invention comprises a surface suitable for contact with bone tissue at the implantation site during use, wherein the surface comprises an outer surface and an inner surface of the biomaterial and / or bone substitute, the inner surface being given by the walls constituting and / or surrounding the pores.

[0134] The surface is wrinkled and / or textured.

[0135] In fact, it is the surface of the structural component (e.g. PMMA), once freed from all the second components or calcium salts, that presents all surfaces, including those of microcavities and macrocavities and tubules, as rough and / or roughened and / or textured. This roughness is formed by the powder of the second component, which remains as an imprint after dissolution.

[0136] As mentioned before, this roughness has a positive function for the biological (bone) tissue which, very similarly to the synthetic material (biomaterial or bone substitute according to the invention), remains in close proximity to it.

[0137] exist Fig. 10A In the figure, the structure of the biomaterial before implantation is visible: the rich network of tubules and pores are evident on a macroscopic scale, both in the form of microcavities (determined by powders with diameters less than 100 microns) and in the form of macrocavities (determined by particles with diameters greater than 200 microns), where powders and particles actually exist in addition to the surface roughness of the material.

[0138] exist Fig. 10B In the Fig. 10A The same material in the , but after the powder and granules of the second material or TCP are dissolved. Removing the second material or TCP enhances and determines both micropores and macropores. At this stage, the roughness is much deeper and has a strong bioaffine to the entire bone-biomaterial interface.

[0139] This does not occur, for example, in the case of a bone cement having the same properties as the first component but without the second component, since bone cement is very compact and its surface is smooth.

[0140] The corrugated and / or textured surface comprises a series of grooves and / or indentations which have a more or less regular curve or spherical cap shape. The size of these grooves and / or indentations is less than 100 microns, as they are left by the imprint of powder particles, e.g. powder particles of the second component, which have a size less than 100 microns.

[0141] In at least one embodiment of the invention, the surface does not have very regular and distinguishable grooves and / or indentations, but the grooves and / or indentations at least partially overlap and form a corrugated surface, which is caused by the presence of valleys or protrusions and grooves and / or indentations.

[0142] However, in another embodiment, the grooves and / or indentations are clearly distinguishable because they are further apart from each other.

[0143] Naturally, the duration of the second period of time may vary widely, depending on the type and solubilization rate of the material constituting the second ceramic component.

[0144] For example, according to one embodiment of the invention (called type 0 if necessary), biomaterials containing calcium sulfate salts exhibit early dissolution, such as 3-6 months; according to a further embodiment (called type 1 if necessary), biomaterials containing calcium carbonate salts have rapid solubility, such as 8-12 months; according to one embodiment of the invention (called type 2 if necessary), biomaterials containing tricalcium phosphate salts have slow solubility, such as 12-24 months; finally, in another embodiment (called type 3 if necessary), biomaterials containing hydroxyapatite salts have very slow solubility, such as more than 24 months.

[0145] The presence of microcavities and tubules, both of which are less than 100 micrometers in size and interconnected in various ways, provides the biomaterial according to the invention with capillary properties. Thus, in use, water or biological fluids are drawn into the biomaterial together with any substance capable of improving or promoting bone regeneration, which determines that bone is regenerated into the macrocavities throughout the biomaterial.

[0146] Furthermore, as will be better explained below, the biomaterial exhibits a uniform and regular capillarity, distributed without interruption throughout the volume of the biomaterial. This result is better than that of currently known materials.

[0147] During the manufacture of the biomaterial according to the invention, the first structural component is in the form of a powder part and a liquid part.

[0148] The powder portion may include at least one of the above-mentioned materials in powder form.

[0149] The particle size of the powder fraction may be between 0.1 micrometer and 500 micrometer.

[0150] The powder portion may have various morphologies and / or may be made of, for example, biocompatible polymethyl methacrylate and / or methyl methacrylate copolymers.

[0151] Furthermore, the powder part may comprise a polymerization catalyst, such as benzoyl peroxide.

[0152] For example, in the case of acrylic resins, the liquid portion includes a monomer, such as MMA, which will polymerize the powdered polymer. The liquid portion may also contain a stabilizer (such as hydroquinone) and a polymerization accelerator, such as NNDT (N,N-dimethyl-p-toluidine), for example, in an amount ranging from 0.000% to 5%.

[0153] For example, considering a biomaterial in solid form according to the present invention, the polymerization promoter (e.g., NNDT) may not be present. In fact, in this case, the biomaterial (and / or the first structural component, e.g., MMA or PMMA) may be polymerized and / or solidified by heating (e.g., in a furnace), effectively eliminating the need for this substance.

[0154] However, this does not occur when considering prior art biomaterials in the form of fluids or pastes, such as those produced directly by the surgeon, since in this case a polymerization promoter must be present.

[0155] The powder portion may include at least one of the above-mentioned materials in powder form.

[0156] For example, in the case of acrylic resin, the powder part may include a polymer powder part that can react with the liquid part and form a specified material by polymerization and / or solidification. For example, the powder part may include a copolymer of polymethyl methacrylate (PMMA) and / or methyl methacrylate (biocompatible), and BP (benzoyl peroxide, which is an indispensable catalyst in at least one embodiment of the present invention).

[0157] BP can be incorporated into PMMA or added as a free powder component and mixed with PMMA.

[0158] To obtain a robust PMMA, the following requirements must be met:

[0159] 1. Eliminate existing structural defects (such as bubbles, etc.). In fact, the larger the bubbles, the worse the mechanical properties.

[0160] 2. Get the conversion (polymerization) percentage as high as possible. In other words, it would be useful to try to convert all of the MMA to PMMA.

[0161] For this reason, or for point 1, it is not enough to remove the air by applying a vacuum. In fact, since the bubbles are dispersed in a fluid with a gradual and initial viscosity, the vacuum does nothing but increase the diameter of the bubbles and, at the same time, evaporate the liquid component MMA with a low vapor pressure, thereby actually increasing the number of bubbles overall.

[0162] However, it has been seen that by increasing the ambient pressure, the diameter of the bubbles decreases to invisible sizes. Fig.13Three samples made of the same resin (first component, e.g. PMMA) polymerized under vacuum (A), ambient pressure (B) and 10 bar pressure (C) were compared. It was observed that sample A contained the largest number of bubbles, sample B contained bubbles but less than sample A, while in sample C the resin was clearly vitrified, as there were no noticeable bubbles.

[0163] exist Fig.14 In the figure, cross-sections of the samples shown above can be seen, and it can be seen that large bubbles are present in sample A, small bubbles are present in sample B, and no bubbles are present in sample C, which samples include the first component according to the present invention.

[0164] In order to increase the conversion of MMA to PMMA after polymerization at room temperature (point 2 above), the sample is heated moderately. In this way, the MMA molecules that are still free but imprisoned and fixed in the PMMA polymer begin to move again due to the effect of thermal energy and polymerize successively. The mechanical properties of the polymer with a high conversion rate are about 10% higher than those of the same polymer with a lower conversion rate.

[0165] Clearly, where there are bubbles there is no material present, which affects the weight of the sample.See, for example, the data reported in Table 4, where 6 samples of each type of sample are compared.

[0166] Table 4: Weights of Samples A, B and C (in grams)

[0167] Sample A Sample B Sample C 1 0.6847 0.8134 0.8561 2 0.6026 0.7939 0.8472 3 0.5518 0.7853 0.8318 4 0.5620 0.8055 0.8212 5 0.6321 0.7973 0.8341 6 0.6436 0.7978 0.8224 average 0.5961 0.7988 0.8355

[0168] As can be seen from the data shown above, the presence of bubbles determines that sample A is about 70% by weight compared to sample C, and sample B is about 95% by weight compared to sample C.

[0169] Table 5 below also shows the compression resistance values ​​exhibited by the above-described samples A, B and C (comparing 6 samples of each type of sample).

[0170] Table 5: Compressive strength of samples A, B and C (in MPa)

[0171] Sample A Sample B Sample C 1 64.45 120.31 144.67 2 73.55 127.92 145.07 3 49.38 128.66 141.29 4 58.90 128.09 145.44 5 77.35 130.96 137.81 6 77.11 128.91 131.65 average 66.79 127.48 140.99

[0172] As can be seen from the data shown above, the presence of bubbles determines that the strength of sample A is about 47% compared to sample C, and the strength of sample B is about 90% compared to sample C.

[0173] Naturally, referring to these samples for the present invention, it must be considered that the material constituting the samples corresponds to the first component of the material according to the invention, in particular, only sample C is produced according to the inventive method envisaged and described herein. However, in samples A, B and C, the second component is absent (while it is present in the biomaterial according to the invention), and therefore the microcavities and macrocavities determined by its presence during polymerization are absent.

[0174] However, the compressive strength trends are also valid considering the presence of the second component, even though the values ​​are altered by its presence. In any case, biomaterials polymerized under positive pressure above ambient pressure have improved mechanical properties of compressive strength compared to polymerizing the same material under ambient pressure or vacuum.

[0175] The method for producing the biomaterial according to the present invention mainly presents the following steps:

[0176] providing a material constituting a first structural component in the form of a powder portion,

[0177] supplying the material constituting the second ceramic component in the form of powder or granules,

[0178] The second ceramic component is mixed with the powder portion of the first ceramic component to obtain a granular mixture of the two components uniformly distributed,

[0179] providing a material constituting a first structural component in the form of a liquid portion,

[0180] adding the liquid portion of the first structural component to the particle mixture,

[0181] mixing the liquid portion and the particle mixture so that the liquid portion reacts with the powder portion of the first structural component to form a biomaterial in a fluid form in which the second ceramic component (which is in a solid form) is uniformly distributed,

[0182] The biomaterial in fluid form is allowed to polymerize and / or cure (eg in a special mold) until it solidifies.

[0183] The method according to the invention advantageously comprises the step of subjecting the biomaterial in fluid form to a positive pressure, for example between +4 and +12 bar, during the polymerization and / or solidification step.

[0184] In this way, the mechanical properties are improved while the capillary properties remain unchanged.

[0185] As can be seen from this specification, there is no bond interaction between the second component (e.g. TCP) and the first structural component (e.g. PMMA). This also explains the mechanical compression behavior of the biomaterial. In fact, the biomaterial comprising the second component (e.g. TCP) provides (at least in one embodiment) a performance that is approximately 10% better than the same biomaterial from which the second component has been removed. The data confirm that during the compression test, the biomaterial is compressed and / or squeezed: if the second component is present, the latter provides moderate resistance, while if the second component has been removed or is not present, the resistance of the biomaterial is only slightly inferior. Therefore, in at least one embodiment of the present invention, the mechanical properties of the biomaterial are mainly determined by the first component and its implementation.

[0186] Micropores and macropores are present in the newly formed biomaterial, so they can coexist with the second component.

[0187] The size of the microcavities and / or macropores is stable and immutable. For example, they do not change when the biomaterial is implanted in vivo. Therefore, what is formed as the second component dissolves and / or is removed is the patency of the pores or at least microcavities and / or macrocavities of the biomaterial according to the present invention.

[0188] According to one embodiment, the polymerizing and / or solidifying step, and the step of subjecting the polymerized and / or solidified biomaterial to positive pressure, may be performed in an autoclave.

[0189] An increase in pressure compared to atmospheric pressure may be caused by gas pressure.

[0190] In this way, the biomaterial in fluid form and at the polymerization and / or solidification stage is compacted when subjected to positive pressure, and gas bubbles that remain entrapped in the material during polymerization and / or solidification are eliminated or significantly reduced.

[0191] Naturally, the presence of gas bubbles in biomaterials has a negative impact both in terms of capillary action (because they actually interrupt the tubules and / or pores present in the biomaterial) and in terms of mechanical properties (because they actually interrupt the structure of the material through the presence of empty spaces caused by the gas bubbles themselves).

[0192] By its nature, the air entrained in the powder at the source and the air introduced as a result of the powder-liquid mixing step is a closed porosity, i.e. each bubble isolates and constitutes an area of ​​weakening of the material. The bubbles destroy the solidity of the material, and in order to improve the mechanical properties of the material, it is necessary to eliminate or at least reduce the bubbles as much as possible.

[0193] Furthermore, due to the pressurization, even moisture droplets present in the biomaterial are prevented from agglomerating by being kept smaller. Smaller droplets correspond to smaller pores, and the fatigue performance of the biomaterial is less degraded. It can be seen that the biomaterial according to the present invention, once implanted in the human body, will last longer in the body.

[0194] In an alternative embodiment, the following step is added to the positive pressure: the biomaterial in liquid or fluid state is polymerized and / or solidified at an elevated temperature, for example a temperature of greater than 50° C. up to about 90° C., or in any case less than 100° C. In this case, the liquid portion of the first structural component may not contain a polymerization accelerator or NNDT. In fact, as previously mentioned, heat increases molecular rotation, thereby increasing the percentage of conversion of monomer to polymer, and therefore actually improves the mechanical properties.

[0195] In yet another embodiment of the present invention, the step of subjecting the biological material to positive pressure and the step of subjecting the biological material to high temperature are performed simultaneously.

[0196] In alternative embodiments, the step of subjecting the biological material to an elevated temperature may occur after the step of subjecting the biological material to a positive pressure.

[0197] In yet another embodiment, the biomaterial is first subjected to positive pressure and after a period of time, even hours if necessary, the biomaterial is also subjected to elevated temperature (maintaining the positive pressure).

[0198] For example, the total time of the step of subjecting the biological material to positive pressure and / or elevated temperature may last up to 12 hours.

[0199] Thus, the polymerized and / or solidified biomaterial is compacted.

[0200] One step of the above method comprises providing a degree of moisture, possibly in the form of water or an aqueous or saline solution, and adding this level of moisture to the particle mixture and / or the first structural component and / or the second ceramic component.

[0201] In one embodiment of the invention, preferably if necessary, a certain humidity level is added to the second ceramic component, thereby obtaining a second wet ceramic component. The second wet ceramic component is then added to the powder portion of the first structural component, followed by the liquid portion of the first structural component.

[0202] The presence of moisture during the polymerization and / or solidification step determines the formation of tubules of the first structural component and / or promotes the mixing step.

[0203] Thus, the biomaterial according to the present invention may contain variable percentage levels of moisture, which may be in the form of water or an aqueous or saline solution.

[0204] According to at least one embodiment of the invention, the biomaterial according to the invention comprises (at least during its initial manufacturing phase) an integral liquid portion comprising or consisting of: a specific humidity level and a liquid portion of said first structural component.

[0205] In particular, the liquid portion generally comprises a moisture level of 25-45%, such as a saline solution, and a liquid portion of 75-55% of the first structural component.

[0206] According to at least one embodiment of the present invention, the biomaterial according to the present invention comprises an integral solid part, which (at least during its initial manufacturing stage or the first time period after implantation) contains or is composed of: a powder part of the first structural component, and powders and granules of the second ceramic component.

[0207] In particular, the integral solid portion comprises 20-80% of the powder portion of the first structural component and 80-20% of the second ceramic component.

[0208] According to one embodiment of the present invention, the total liquid portion is equivalent to about 30-70 grams and is added to 100 grams of the total solid portion.

[0209] The biomaterial according to at least one embodiment of the present invention is a composite of a solid substance made of the first structural component and the second structural component (e.g. PMMA and TCP), which must coexist with an immiscible liquid substance [e.g. water, and, for example, a solvent or MMA (methyl methacrylate)].

[0210] Water or moisture can be dispersed partly in the form of droplets during mixing (this will produce small tubes) and partly adsorbed on the second component or TCP. During mixing, air can also be incorporated, which is dispersed in the form of bubbles, for example.

[0211] Bullous materials are discontinuous materials with inherent mechanical weaknesses.Thus, due to the pressurization of the present method, the structural integrity of the biomaterial according to the present invention is repaired and improved.

[0212] In fact, any bubbles of air and / or water or moisture present in the fluid substance are compressed, thereby significantly reducing their volume and / or size. This provides the biomaterial with better mechanical properties.

[0213] Experimental testing

[0214] exist Figure 3 In the figure, a part of an adult pig femoral condyle is shown by way of example, wherein a sample A1 formed according to the biomaterial of the present invention has been inserted 12 months ago (e.g., type 2, including TCP, e.g., wherein the first structural component is acrylic resin and / or PMMA). Sample A1 before implantation is white.

[0215] Figure 3 Reference numeral 2 in FIG. 1 represents sample A1, but since it is implanted, it is no longer white but has the same color as the surrounding spongy bone (in Figure 3 The biomaterial is enriched with bone marrow fat and capillaries because it has been invaded by them. Figure 3 The spongy bone 1 in the specimen closely surrounds the specimen A1, in fact, it penetrates into the specimen and has a bright vermilion color, indicating that it is a living tissue that regenerates without any interference from the presence of biological material. Even the cortical bone (in Figure 3 3) also allows its remodeling to adapt to the presence of biological material of sample A1 without the need to insert a fibrotic membrane.

[0216] Figure 4 Four samples (with cubic construction) are shown for performance comparison, where:

[0217] The sample denoted by No. 1 includes a porous ceramic material made of hydroxyapatite and TCP;

[0218] The sample denoted by No. 2 includes the biomaterial according to the present invention (e.g., acrylic resin and / or PMMA combined with TCP), wherein the first structural component and the second ceramic component are still present;

[0219] The samples denoted by 3 and 4 comprise a biomaterial according to the invention in which the second ceramic component has been resorbed and is therefore no longer present (in this mode the biomaterial is also referred to as demineralised).

[0220] Figure 4 Samples No. 3 and No. 4 in the Figure simulate the long-term in vivo conditions of the biomaterial according to the present invention, ie, when in use, for example, the biological fluid has completely dissolved the second ceramic component (TCP in the specific example).

[0221] Figure 5 Shows Figure 4 Image of sample 3 with some of the pores digitally highlighted. This confirms the porosity of the demineralized biomaterial. It can be seen that the porosity is comparable to that of sample 1.

[0222] Figure 6 This explains the above Figure 4 Mechanical properties of samples No. 1 and No. 3 compared as shown in .

[0223] In particular, we note the two metal plates of the compression tester, which crushed and destroyed sample No. 1 made entirely of ceramic (left), while they crushed and simply deformed sample No. 3 made of an example of a biomaterial according to the present invention (right). Note that the crushing resulted in an almost explosive brittle failure with multiple fragments falling off sample No. 1. However, sample No. 3 deformed significantly under the strong load (at least twice as much as sample No. 1 supported by ceramic) but remained compact and did not release fragments.

[0224] From a surgical point of view, this significant difference means that when a ceramic insert (such as that corresponding to specimen No. 1) is implanted, it is exposed to the risk of fragile fracture for a long time (until it completely dissolves), with the result that many fragments are released, which can migrate into the biological fluid, accumulate in serous bags and cause bursitis, foreign body arthritis, joint degeneration, etc. In contrast, the biomaterial according to the invention (which corresponds to, for example, the biomaterial of specimen No. 3) can deform under mechanical load - even highly deform - but without causing damage to the tissue or joint close to the implantation site, since no fragments are left.

[0225] The results of the compression test can be found in Figure 7 in the chart.

[0226] Furthermore, by converting the raw data of the load and subsequent trips for this chart, the following results can be highlighted:

[0227] sample Maximum compressive strength (MPa) <![CDATA[Cross-section (mm 2 ) <!-- 15 -->]]> No. 1 22.98 93.51 No. 2 71.53 81.02 No.3 62.92 90.80 No. 4 55.27 85.26

[0228] Figure 4 The compressive strength of sample No. 1 is very low, about 23 MPa. Figure 4 Sample No. 2 in the sample has the largest compressive strength, which is about 72 MPa, because in addition to the first structural component, the biomaterial also contains the entire second ceramic component, which fills the cavities or pores and imparts high compression resistance. Figure 4 The compressive strengths of samples No. 3 and No. 4 in the test piece are approximately 63 MPa and 55 MPa, respectively. Figure 4 Samples 3 and 4 in the example were demineralized and no longer had the second ceramic component in the form of powder or granules in the cavity of the first structural component, and therefore failed earlier than sample No. 2. However, the compressive strength of these samples was at least about 2.5 times higher than that of sample No. 1.

[0229] Thus, the compressive strength of the biomaterial according to the invention is higher than 55 MPa, or higher than 60 MPa, or higher than 70 MPa, depending on the degree of dissolution of the second ceramic component relative to the first structural component, which, as mentioned above, is permanent and insoluble.

[0230] The compressive strength data were measured according to the ISO 5833 standard, 2nd edition, dated 05-01-2002, in particular according to the section called "Determination of compressive strength of polymerized cement".

[0231] The test involves preparing a cylinder of the material to be tested (approximately 12 mm long and 6 mm in diameter) and applying it to a testing machine capable of applying and measuring a compressive force (load) of at least 4 kN, the machine being equipped with a system capable of recording the movement of the load relative to the crosspiece or crosshead of the cylinder.

[0232] The cylinder is placed in the testing machine and the machine is operated at a constant crosshead speed to produce a displacement curve versus load. The test ends when the cylinder breaks or exceeds the upper yield point.

[0233] For each cylinder, to calculate the compressive strength, the force applied to cause fracture, or the load at 2% offset ("2% offset load"), or the load at the upper sliding limit (whichever occurs first), is divided by the original cross-sectional area of ​​the cylinder (in mm). 2 The quotient is expressed as the compressive strength in MPa.

[0234] The test is conducted by maintaining the material to be tested and the equipment at a temperature of 23 ± 1°C; and testing the cylinders approximately 24 hours after mixing the material to be tested.

[0235] Experimental data have shown that the capillary action of samples of the same material polymerized and / or solidified at positive pressure (e.g. +7 bar (e.g. at room temperature or equal to 23°C) is improved compared to the same material polymerized and / or solidified at atmospheric pressure (1 bar and room temperature or 23°C).

[0236] Furthermore, the rate at which a sample of biological material polymerized and / or coagulated under positive pressure (eg +7 bar) absorbs liquid by capillary action is also improved compared to the same material polymerized and / or coagulated under atmospheric pressure.

[0237] In addition, since the space occupied by bubbles and / or water droplets is significantly reduced and / or their size is significantly reduced, the absorption of liquid by capillary action in the biological material sample polymerized and / or coagulated under positive pressure (e.g. +7 bar) is more regular and uniform / homogeneous compared to the same material polymerized and / or coagulated under atmospheric pressure.

[0238] Subsequently, the polymerized and / or solidified biomaterial according to the invention (eg, on a sample with a size of 6.8 mm x 12 mm) is subjected to a further compression test.

[0239] In particular, while known types of materials have a compressive strength of about 35-36 MPa, the average compressive strength of the polymerized and / or solidified biomaterial according to the invention is equal to 60 MPa, or greater than 60 MPa, or greater than 61 MPa, with a standard deviation of about 3 MPa. The compressive strength can reach values ​​even higher than 67-75 MPa.

[0240] According to at least one embodiment of the invention, these data were carried out on samples in which the first structural component was formed of acrylic resin and / or polymethyl methacrylate (PMMA) and contained powders and granules of the second ceramic component, in particular TCP.

[0241] These data demonstrate that the biomaterial according to the present invention has improved mechanical and capillary properties compared to prior art materials or to the same material polymerized and / or solidified at atmospheric pressure.

[0242] The biomaterial according to the invention is used as a reconstructive material, acting as a bone substitute or filling material, and is placed in a cavity or gap or bone atrophy. As can be seen, due to the material properties described above, such gaps or atrophies can also have considerable dimensions. In addition, compared to known materials, the biomaterial according to the invention is able to improve and promote the reconstruction of bone tissue around the implantation site, as well as to form a perfectly integrated and functional blood circulation, even within the biomaterial itself.

[0243] By means of capillary action, the biomaterial according to the invention is able to absorb various types of fluids, gaseous substances, and / or water, or other biological fluids and / or drugs and medical substances. The biomaterial is then able to release these substances again and make them available in the body.

[0244] Due to its porous nature and its ability to absorb liquids by capillary action, the biomaterial according to the invention can be advantageously used as a drug release system (drug delivery system) in order to contain and deliver active ingredients (which also have a pharmaceutical function) at the site of placement.

[0245] In further embodiments, the biomaterials described above may be supplemented with radiopaque materials (eg, barium sulfate and / or other known radiopaque materials).

[0246] The biomaterial or bone substitute according to the invention comprises at least one drug or medical substance, or may be added with at least one drug or medical substance. The at least one drug or medical substance may be initially present in the first structural component and / or the second ceramic component, and / or may be subsequently introduced into the biomaterial by impregnation, addition, spraying, etc. In this way, the biomaterial according to the invention may help, for example, to combat infections in bones and / or tissues present near the implantation site.

[0247] In one embodiment of the present invention, the at least one drug or medical substance may include at least one antibiotic, such as gentamicin, vancomycin, tetracycline, etc., or a combination thereof.

[0248] The at least one drug or medical substance may be initially present in the biomaterial according to the invention, for example it may be incorporated therein by mixing it with the first structural component and / or the second ceramic component during the manufacturing stage.

[0249] Alternatively, the biomaterial or bone substitute may initially be free of at least one drug or medical substance and immersed in a solution containing the at least one drug or medical substance by a surgeon prior to implantation. In this case, the biomaterial absorbs at least one substance prior to implantation and releases it for use after implantation.

[0250] According to a further embodiment, the biomaterial or bone substitute may contain at least one (first) drug or medical substance, and before implantation, the surgeon may decide to add at least one (second) drug or medical substance by impregnation and / or immersion, which is the same as or different from the first drug or medical substance, depending on the specific surgical needs and the needs of the patient.

[0251] The present invention also relates to following system, wherein the biomaterial according to the present invention is present in solid and liquid form simultaneously. In detail, as previously mentioned, the biomaterial in solid form can be positioned at the implantation site when in use, and the biomaterial in fluid form can be used to fix the biomaterial in solid form in place (because it can harden). In this way, after hardening and / or polymerization and / or solidification, the pores of the biomaterial in solid form (provided by tubules, microcavities and macrocavities) and the pores of the biomaterial in fluid form (given by tubules, microcavities and macrocavities) exist in space and fluid continuity.

[0252] Unlike what would happen when using, for example, traditional bone cement (which does not have sufficient porosity and thus can form a fibrous sheath at the interface with bone tissue), using a fluid-form biomaterial to fix a solid-form biomaterial, and allowing the fluid-form biomaterial to solidify, allows the pores to be continuous throughout the implant material, thereby further promoting bone regeneration.

[0253] The biomaterial in fluid form may be the same as the biomaterial in solid form (except that the former is in a fluid state), or may differ from the biomaterial in solid form in terms of the amount and / or type of the second ceramic component.

[0254] As an alternative or additional embodiment, the biomaterial in fluid form may differ in the amount and / or type of material occupying the first structural component compared to the biomaterial in solid form.

[0255] As an alternative or additional embodiment, the biomaterial in fluid form may differ compared to the biomaterial in solid form due to the amount and / or type of drug or medical substance and / or radiopaque material.

[0256] Thus, the (coagulating) biomaterial in fluid form acts as a glue for the biomaterial in solid form.

[0257] The biomaterial in fluid form is in the form of a paste which is injectable (eg using an extrusion syringe) or the paste can be applied via standard methods currently used for known materials, for example by using a spatula.

[0258] The fact that the biomaterial can be present in this fluid form is imparted by the property that the first structural component can be in fluid form and solidify after application within a predetermined, relatively short period of several minutes compared to known materials.

[0259] In this case, the biomaterial in fluid form may include a polymerization promoter in its composition, while the biomaterial in solid or preformed form may be present or absent a polymerization promoter in order to achieve.

[0260] The invention thus conceived is susceptible of numerous modifications and variations, all of which fall within the scope of the inventive concept.

Claims

1. A biomaterial which is composite, biocompatible, osteoinductive and / or osteoconductive, suitable for use as a bone substitute during use, for filling lesions, gaps, or bone cavities, or for tissue function restoration where it is necessary to replace or repair bone tissue, comprising a first structural component and a second ceramic component, the first structural component being of a permanent and non-absorbable type for use in the human body, wherein the first structural component comprises an organic, plastic and / or polymeric material, the second ceramic component being of a soluble or solubilizing type for use in contact with a liquid, such as a biological liquid, wherein the first structural component comprises interconnected pores comprising pores and / or tubules with a diameter of less than 100 microns, wherein the second ceramic component is encapsulated in the pores, comprising at least one calcium salt, characterised in that the biomaterial is in a preformed solid form and has a compressive strength greater than 55 MPa, the compressive strength being measured according to the second edition of ISO 5833 standard dated 01-05-2002.

2. The biomaterial according to claim 1, wherein the biomaterial is compact and / or has a three-dimensional sphere, hemisphere, polyhedron, parallelepiped, hexahedron, truncated cone or truncated pyramid, cone or pyramid, parallel structure, block, wedge-shaped structure, or irregular three-dimensional shape.

3. The biomaterial according to claim 1 or 2, wherein the compressive strength of the biomaterial is greater than 60 MPa, or greater than 70 MPa, or greater than 67-75 MPa, and the compressive strength is measured according to the ISO5833 standard, second edition, dated 01-05-2002.

4. A biomaterial according to any of the preceding claims, wherein the second ceramic component is in the form of a powder having a size less than 100 μm, and a granular material having a size between 100 μm and 500 μm, or between 200 μm and 500 μm, or between 100 μm and 2000 μm, or between 200 μm and 2000 μm, and / or wherein the calcium salt of the second ceramic component comprises a compound based on calcium phosphate (CP), calcium sulfate (CS), calcium carbonate (CC), wherein the calcium phosphate compound comprises at least one or more of the following: monocalcium phosphate monohydrate (MCPM), monocalcium phosphate anhydrous (MCPA), monocalcium phosphate dihydrate (DCPD), monocalcium phosphate anhydrous (DCP), octacalcium phosphate (OCP), α-tricalcium phosphate (α-TCP), β-tricalcium phosphate (β-TCP), hydroxyapatite (HA), tetracalcium phosphate (TTCP).

5. A biomaterial according to any of the preceding claims, wherein the second ceramic component is uniformly distributed throughout the volume occupied by the biomaterial, at least during a first period of use after implantation.

6. Biomaterial according to the preceding claim, which after the first period of use after the implantation can no longer contain the second ceramic component, because the second ceramic component used has dissolved and / or solubilized.

7. A biomaterial according to any of the preceding claims, wherein the first structural component comprises pores further comprising microcavities having a size of less than 100 microns, and macrocavities having a size of between 100 and 500 microns, or between 200 microns and 500 microns, or between 300 microns and 500 microns, or between 100 microns and 2000 microns, or between 200 microns and 2000 microns, or between 300 microns and 2000 microns, or greater than 250 microns and up to 2000 microns, or greater than 500 microns and up to 2000 microns, wherein the pores are interconnected and uniformly distributed throughout the volume occupied by the biomaterial, and / or wherein the second ceramic component, in use, is encapsulated within the pores formed by the microcavities and macrocavities of the first structural component, at least during a first period of use after implantation.

8. A biomaterial according to any of the preceding claims, wherein the organic, plastic, and / or polymeric material of the first structural component comprises or consists of a plastic material, a plastic or acrylic or methacrylic resin, or a plastic or acrylic polymer, or a bone cement made of polymethyl methacrylate (PMMA) and / or a copolymer based on methyl methacrylate, or a thermoplastic polymer, polyethylene, polypropylene, polyester, a thermoformable polymer, or other similar material.

9. The biomaterial according to any of the preceding claims, comprising a moisture level in the form of water or an aqueous or saline solution, and / or comprising at least one radiopaque material, and / or comprising a drug or medical substance, such as at least one antibiotic.

10. Method for producing a biomaterial according to one or more of the preceding claims, wherein the biomaterial is composite, biocompatible, osteoinductive and / or osteoconductive, the biomaterial being suitable for use as a bone substitute during use, for filling lesions, gaps, or bone cavities, or for repairing tissue functions where it is necessary to replace or repair bone tissue, the biomaterial comprising a first structural component and a second ceramic component, the first structural component being of a permanent and non-absorbable type for use in the human body, the second ceramic component being of a soluble or solubilized type for use in contact with a liquid, such as a biological liquid, the method comprising the following steps: providing the first structural component comprising an organic, plastic, and / or polymeric material, wherein the first component comprises a powder portion and a liquid portion, wherein the powder portion comprises a polymeric powder portion capable of reacting with the liquid portion, providing the second ceramic component comprising at least one calcium salt, mixing said second ceramic component together with said powder portion of said first ceramic component so as to obtain a granular mixture in which the two components are uniformly distributed, adding the liquid portion of the first structural component to the particle mixture, mixing the liquid portion with the particle mixture so that the liquid portion reacts with the powder portion of the first structural component to form a biomaterial in a fluid form, wherein the second ceramic component is uniformly distributed in the biomaterial in a fluid form, polymerizing and / or solidifying the biomaterial in fluid form until it solidifies, for example in a special mold, and / or in an oven, and / or in an autoclave, polymerizing and / or solidifying the biomaterial in fluid form until it solidifies, subjecting the biomaterial in fluid form to a positive pressure, for example between +4 and +12 bar, so as to compact the biomaterial and reduce the volume and / or size of bubbles of air and / or water or the moisture present in the biomaterial and possibly entrained in the biomaterial during the polymerization and / or solidification step, Said biomaterial is obtained in the form of a preformed solid having a compressive strength greater than 55 MPa, measured according to the ISO 5833 standard, 2nd edition, dated 01-05-2002.

11. The method of claim 10, wherein the step of subjecting to positive pressure occurs during the step of polymerizing and / or solidifying.

12. The method of claim 10 or 11, wherein the subjecting step further comprises subjecting the biological material in fluid form to an elevated temperature of less than 100°C.

13. The method according to one or more of claims 10 to 12, wherein the step of providing the second ceramic component comprises providing the second ceramic component in the form of a powder having a size less than 100 microns, and in the form of granules having a size between 100 microns and 500 microns, or between 200 microns and 500 microns, or between 300 and 500 microns, or between 100 microns and 2000 microns, or between 200 microns and 2000 microns, or between 300 microns and 2000 microns, or greater than 250 microns up to 2000 microns, or greater than 500 microns up to 2000 microns; and / or comprises the steps of providing a moisture level in the form of water, or an aqueous solution, or a saline solution, and adding the moisture level to the second ceramic component, thereby obtaining a second wet ceramic component, and adding the second wet ceramic component to the powder portion of the first structural component, followed by the step of adding the liquid portion of the first structural component.

14. The method according to one or more of claims 10 to 13, comprising the step of adding at least one radiopaque material, and / or a drug or medical substance such as at least one antibiotic to the first structural component, and / or to the powder part of the first structural component, and / or to the liquid part of the first structural component, and / or to the second ceramic component, and / or comprising the step of immersing the biomaterial in a solution comprising at least one drug or medical substance.

15. A kit for filling lesions, gaps, or bone cavities, or for tissue function repair where it is necessary to replace or repair bone tissue, the kit comprising a biomaterial as claimed in any of claims 1 to 9 in a preformed solid form, and a biomaterial in a fluid form, wherein the biomaterial in a fluid form comprises a first structural component in the form of a coagulating fluid, and a second ceramic component, wherein the first structural component in the fluid form is the same or different from the first structural component of the biomaterial in a preformed solid form, and the second ceramic component of the biomaterial in a fluid form is the same or different from the second ceramic component of the biomaterial in a preformed solid form.

16. A kit according to the preceding claim, wherein the biomaterial in fluid form acts as a glue and adhesive for the biomaterial in preformed solid form in the implantation site when in use.

17. Use of the biomaterial according to any one of claims 1 to 9, or use of the kit according to claim 15 or 16, as a bone substitute, for filling lesions, gaps, or bone cavities, or for tissue function repair where it is necessary to replace or repair bone tissue, such as for large bone gaps or cavities, large lesions caused by combat injuries, large tumors, large trauma, etc.

18. A bone substitute for filling bone lesions, gaps, or cavities, or for tissue function restoration where it is necessary to replace or repair bone tissue, for example for large bone gaps or cavities, large lesions caused by combat injuries, large tumors, large trauma, etc., said bone substitute comprising a first structural component, which is of permanent and non-absorbable type, for use in the human body, wherein said first structural component comprises an organic, plastic, and / or polymeric material, wherein said first structural component comprises interconnected pores, said interconnected pores comprising pores and / or tubules with a diameter of less than 100 microns, microcavities with a size of less than 100 microns, and macrocavities, wherein at least some of said microcavities and said macrocavities are suitable for encapsulating a second ceramic component, said second ceramic component being of soluble or solubilizing type, wherein said pores are uniformly distributed throughout the volume occupied by said bone substitute, characterised in that said biomaterial is in the form of a preformed solid and has a compressive strength greater than 55 MPa, said compressive strength being measured according to ISO 5833 standard 2nd edition dated 01-05-2002.

19. A bone substitute according to claim 18, wherein the bone substitute is obtainable by the biomaterial according to any one of claims 1 to 9, and / or by the method according to any one of claims 10 to 14, and / or wherein the microcavities and the macrocavities become hollow during use by solubilization of the second ceramic component, the second ceramic component being of a soluble or solubilized type and in contact with water or a liquid during use, the liquid being, for example, a biological liquid, wherein the second ceramic component comprises at least one calcium salt.

20. The bone substitute according to claim 18 or 19, wherein the macrocavity size is between 100 and 500 microns, or between 200 and 500 microns, or between 300 and 500 microns, or between 100 and 2000 microns, or between 200 and 2000 microns, or between 300 and 2000 microns, or greater than 250 microns up to 2000 microns, or greater than 500 microns up to 2000 microns.

21. A bone substitute according to any one of claims 18 to 20, wherein the first structural component comprises a surface adapted to contact bone tissue at the implantation site during use, wherein the surface comprises an outer surface of the bone substitute, and an inner surface, the inner surface being provided by a wall constituting and / or surrounding the pores, wherein the surface is corrugated and / or textured.